Improvement of justification of sequence of construction of buildings and constructions - O. V. Demidenko; S. M. Kuznetsov (Вестник СибАДИ)
This paper proposes a method for estimating the risk of organizational and technological construction, transport technology and mechanized processes. Leading processes for construction and installation work are machines and mechanisms. For the successful implementation of the production program of the construction company must be a joint operation of reliable transport and process, construction crews, construction machines and mechanisms. The developed model study of priority construction of buildings and structures allows to more reliably determine the duration of construction, more efficient use of vehicles, construction vehicles and crews by their rhythmic and smooth operation.